1901 Mich. Pub. Acts 336 - (:unkn) unknown (My University, 1901)
An Act to Revise and Amend the Laws for the Protection of Game and Birds, § 11: Nor shall any person or persons make use of any swivel or punt gun for the killing of any water fowl, or make use of any battery, sink boat or similar device whatever, save only a gun of not greater size than ten caliber, such gun to be held in the hands at the time firing[.]
Keywords: HUNTING REGULATION